Unexpected Abscess Localization of the Anterior Abdominal Wall in an ADPKD Patient Undergoing Hemodialysis. (2nd August 2015) - Sabanis, Nikos; Paschou, Eleni; Gavriilaki, Eleni; Mourounoglou, Maria; Vasileiou, Sotirios
Abstract : Autosomal Dominant Polycystic Kidney Disease (ADPKD) is one of the most common monogenic disorders and the leading inheritable cause of end-stage renal disease worldwide. Cystic and noncystic extrarenal manifestations are correlated with variable clinical presentations so that an inherited disorder is now considered a systemic disease. Kidney and liver cystic infections are the most common infectious complications in ADPKD patients. Furthermore, it is well known that ADPKD is commonly associated with colonic diverticular disease which recently has been reported to be linked to increased risk of infection on hemodialysis patients. Herein, we present a case of anterior abdominal wall abscess caused by Enterococcus faecalis in a patient with ADPKD undergoing hemodialysis. Although the precise pathway of infection remains uncertain, the previous medical history as well as the clinical course of our patient led us to hypothesize an alternative route of infection from the gastrointestinal tract through an aberrant intestinal barrier into the bloodstream and eventually to an atypical location.